Development and application of a new biological nano-selenium fermentation broth based on Bacillus subtilis SE201412 - Huang, Sisi; Yu, Kan; Wen, Liang; Long, Xiaoling; Sun, Jin; Liu, Quxiao; Zheng, Zhuo; Zheng, Wei; Luo, Hongmei; Liu, Jinlong (Scientific reports, 2023)
In order to improve the functionality and additional value of agricultural products, this study developing nano-selenium fermentation broth and established a new application strategy of bio-nano-selenium by screening and identifying selenium-rich microorganisms. We isolated a new strain from tobacco waste and named it Bacillus subtilis SE201412 (GenBank accession no. OP854680), which could aerobically grow under the condition of 66,000 mg L −1 selenite concentration, and could convert 99.19% of selenite into biological nano-selenium (BioSeNPs) within 18 h. Using strain SE201412, we industrially produced the different concentrations of fermentation broth containing 5000–3000 mg L −1 pure selenium for commercial use. The synthesized selenium nanoparticles (SeNPs) were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and nanoparticle tracking analysis (NTA). TEM and SEM results showed that SeNPs were distributed outside cells. NTA assay of fermentation broth indicated that the nanoparticles were spherical with an average particle size of 126 ± 0.5 nm. Toxicity test revealed that the median lethal dose (LD 50 ) of the fermentation broth to mice was 2710 mg kg −1 , indicating its low toxicity and high safety. In addition, we applied BioSeNP fermentation broth to rice and wheat through field experiments. The results showed that the application of fermentation broth significantly increased the total selenium content and organic selenium percentage in rice and wheat grains. Our findings provide valuable reference for the development of BioSeNPs with extensive application prospects.